Pengaruh Pendidikan Kesehatan dengan Metode Demonstrasi terhadap Tingkat Pengetahuan Remaja Putri tentang Pemeriksaan Payudara Sendiri (Sadari) Kelas VIII di SMPN 02 Padamara - Wulan Margina; Gita Lestari (LPPM Universitas Bhamada Slawi PSDKU D III Kebidanan Kampus Kota Pekalongan, 2025)
Reporting from the Global Burden of Cancer (GLOBOCAN) data, it was recorded that deaths caused by breast cancer in 2018 reached 18.1 million cases and will increase by 9.6 million per year. The high prevalence of breast cancer in Indonesia is due to the lack of knowledge and the low rate of early breast cancer prevention. Breast self-examination is very effective, efficient, and can be done alone which aims to detect breast cancer early. Understand the effect of the level of understanding of adolescent girls before and after being given health education with demonstration methods related to breast self-examination (SADARI) at SMPN 2 Padarama. The design used in this study was a pre-experimental design type one group pretest posttest with a sample of 66 adolescent girls through simple random sampling method. Analyzed using the Wilcoxon statistical test with a significance level of α ≤ 0.05 used to determine differences in the results of knowledge of adolescent girls before and after being given health education using demonstration techniques. The results of the study with the Wilcoxon statistical test showed that the p-value was 0.000 <0.05 so that there were differences in the level of knowledge of adolescent girls about SADARI before and after being given health education through demonstration techniques. It is expected that the school can cooperate with health workers and be able to facilitate female students by providing health education through demonstration techniques, demonstration methods have proven effective in increasing the knowledge of adolescent girls.